PENGARUH MODEL PBL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 34 PONTIANAK - Devi, Devi; Bistari, Bistari; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to analyze the influence of Problem Based Learning model towards the learning outcomes in Mathematics subject of fourth grade students of Sekolah Dasar Negeri 34 Pontianak Kota.. The method used in this study was Quasi Experiment Design research using nonequivalent control group design. The population was all fourth grade students of Sekolah Dasar Negeri 34 Pontianak Kota, Sampling was using Purposive Sampling technique, namely IVC class and IVD class at Sekolah Dasar Negeri 34 Pontianak Kota. Based on the data analysis, the results of the post-test average of students in the control class were 56.25 and the results of the post-test average of students in the experimental class were 69.81. After t test is obtained tcount 2.338 while t table is 1.999, it turns out tcount ≥ ttable or 2.389 ≥ 1.999 which means that there is a significant effect on the application of Problem Based models Learning. The results of the effect size data calculation from the both experimental and control classes were 0,557. This means that the application of the Problem Based Learning model has a moderate influence on the mathematics learning outcomes of fourth grade students of Sekolah Dasar Negeri 34 Pontianak Kota. Keywords: Hasil Belajar, Matematika, Model PBL